The Odyssey of ʿAjamī and the Swahili People - Mugane, John (Islamic Africa, 2017)
This paper takes a look at the odyssey of the Arabic script in Swahili hands. It shows how the distinction between the Arabic script and Swahili ʿAjamī constitutes a hyphen whose meaning is saturated with the story of Swahili society and language. The hyphen represents a non-trivial record of Swahili agency as innovative users, authors, transcribers, translators, and interpreters of the Arabic script enlarged its use and versatility as a viable medium to write Swahili, a Bantu language. The paper identifies as resilience Swahili efforts to sustain the use of the unmodified Arabic script alongside the enriched one. The Swahili wrote because they were compelled to write, everyone in their dialect, with content not divorced from script. The Swahili ʿAjamī record is a bonafide source and terminus of Africa’s knowledge.